Effectiveness of Several Extraction Methods on the Quality of the Seeds of Two Determinate Tomato (Solanum lycopersicum Mill.) Varieties - Yulianti, Fitri (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2019)
Tomato (Solanum lycopersicum Mill.) seeds have pulp which is inhibit for the tomato seed itself. Pulp stick on the seed will prevent the seed from germination. This research aims was to find out the effective technique of Tymoti and Tantyna varieties seed extraction. This research was conducted at Laboratory and Greenhouse, F6 Campus Gunadarma University located at Depok from October 2018 to January 2019. The experimental design arranged factorial in a Randomized Complete Block Design (RCBD), consisting of two factors with three replications. The first factor was varieties (Tymoti and Tantyna) and the second factor was treatment of seed extraction techniques; (calcium oxide (CaO) 10 g/l and 15 g/l for 20 minutes, and water fermentation technique for 12 hours and 24 hours). Data was analyzed using analysis of variance (F test) at 5% level. If the F-test showed significant difference, then it will be followed by HSD-test (Honestly Significant Difference) at 5% level. The results of the experiments showed that the characteristics of fruit size and tomato dimensions of Tymoti and Tantyna varieties were significantly different. The single factor of varieties also caused differences in weight of 100 seeds, percentage of seed growth rate, and percentage of seed vigor index. While the single factor of seed extraction methods did not show significant difference in the physiological quality of the seeds of the two determinate vegetable tomato varieties tested.